Seasonal nitrogen dynamics in lowland rice cropping systems in inland valleys of northern Ghana. Issue 1 (19th December 2016) - Asante, Michael; Becker, Mathias; Angulo, Carlos; Fosu, Mathias; Dogbe, Wilson
Abstract: Farmers in the inland valleys of northern Ghana are challenged with nitrogen (N) deficiency as a major production constraint of rainfed lowland rice ( Oryza sativa L.). With extremely low use of external inputs, there is a need to efficiently use the systems' internal resources such as native soil N. Largest soil nitrate‐N losses are expected to occur during the transition between the dry and wet season (DWT) when the soil aeration status changes from aerobic to anaerobic conditions. Technical options avoiding the build‐up of nitrate are expected to reduce N losses and may thus enhance the yield of rice. A field study in the moist savanna zone of Ghana assessed the in situ mineralization of native soil N, the contribution of nitrate to the valley bottom by sub‐surface flow from adjacent slopes, and the effects of crop and land management options during DWT on seasonal soil Nmin dynamics and the yield of lowland rice. Large amounts of nitrate accumulated during DWT with a peak of 58 kg ha −1 in lowland soils, of which 32 kg ha −1 were contributed from the adjacent upland slope. Most of this nitrate disappeared at the onset of the wet season, possibly by leaching and denitrification upon soil flooding. While the incorporation of rice straw (temporary immobilization of soil N in the microbial biomass) had little effect on soil N conservation, growing a crop during DWT conserved 22–27 kg of soil N ha −1 in the biomass and Crotalaria juncea supplied an additional 43 kg N ha −1 from biological N2 fixation. Farmers' practice of bare fallow during DWT resulted in the lowest rice grain yield that increased from 1.3 (2.2) to 3.9 t ha −1 in case of the transition‐season legume. Growing a pre‐rice legume during DWT appears a promising option to manage N and increase lowland rice yields in the inland valleys of northern Ghana.